2015
DOI: 10.1038/ngeo2508
|View full text |Cite
|
Sign up to set email alerts
|

Saturn’s F ring and shepherd satellites a natural outcome of satellite system formation

Abstract: Saturn's F ring is a narrow ring of icy particles, located 3,400 km beyond the outer edge of the main ring system. Enigmatically, the F ring is accompanied on either side by two small satellites, Prometheus and Pandora, which are called shepherd satellites 1-3 . The inner regular satellites of giant planets are thought to form by the accretion of particles from an ancient massive ring and subsequent outward migration 4-7 . However, the origin of a system consisting of a narrow ring and shepherd satellites rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Thus, outgassing of dust particles from the surface may occur (Pan & Wu 2016). Also, a partial disruption of a primordial differentiated object through an extreme close encounter with a giant plant may directly form debris and satellites around the remnant objects (Hyodo et al 2016) and a long-term dynamical evolution may shape the debris to the observed narrow structures (Hyodo & Ohtsuki 2015). Either of the proposed scenario may apply to one of the observed ringed small objects, but further observations and investigations are required to constrain more about their physical properties and their origins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, outgassing of dust particles from the surface may occur (Pan & Wu 2016). Also, a partial disruption of a primordial differentiated object through an extreme close encounter with a giant plant may directly form debris and satellites around the remnant objects (Hyodo et al 2016) and a long-term dynamical evolution may shape the debris to the observed narrow structures (Hyodo & Ohtsuki 2015). Either of the proposed scenario may apply to one of the observed ringed small objects, but further observations and investigations are required to constrain more about their physical properties and their origins.…”
Section: Discussionmentioning
confidence: 99%
“…Currently it is unclear if the F ring and its shepherd moons formed at this radial location, because it is close to the Roche limit or purely a coincidence. Hyodo & Ohtsuki (2015) showed that the F ring and its shepherd moons were a natural outcome of a collision between two satellites at its current location. If such a collision occurred at a larger radial distance than the current location of the F ring, it would place it in a lower tidal environment but still with nearby shepherd moons.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also implies that hit-and-run collision between similar-sized objects were frequent throughout the formation of the small inner moons. Such an event was proposed to generate the F ring 6 . Although a hit-and-run event between Prometheus and Pandora was previously considered to explain the origin of the F ring, in our model the F ring material could originate from the hit-and-run collision of the precursors of Prometheus, then be trapped in the stability area between Pandora and Prometheus after the merging of the precursors.…”
mentioning
confidence: 99%